Determining the effects of the FEMA Community Rating System program on flood losses in the United States. (March 2017) - Highfield, Wesley E.; Brody, Samuel D.
Abstract: Among all natural hazards inflicting the United States floods continue to impose the most economic disruption. Increasing physical risk coupled with development in flood-prone areas has amplified the adverse economic and human impacts of flooding. In an effort to counter mounting flood losses, the U.S. Federal Emergency Management Agency introduced the Community Rating System in 1990 as a way to incentivize local jurisdictions to exceed the existing minimum standard for floodplain management. In response to the lack of comprehensive knowledge on the effectiveness of the CRS, this study quantitatively evaluates the difference in flood losses experienced by CRS-participating communities. We pose the following research question: do CRS communities incur lower losses than non-CRS communities when accounting for contextual environmental and socioeconomic characteristics? Results from a two-step analysis consisting of propensity score matching and pooled linear regressions indicate that the CRS program has had a statistically significant effect on reducing the amount of insured flood losses incurred by communities across the U.S. In addition to receiving discounts on insurance premium rates, communities participating in the CRS also experienced a 41.6% overall average reduction in flood claims compared to communities with similar characteristics that do not participate.